Intracranial Solitary Fibrous Tumor with Concurrent Meningioma: Case Report and Review of the Literature - Joaquin Vega Gonzales-Portillo; Marco Gonzales-Portillo Showing; Luis A. Huamán Tanta; Sandro Casavilca Zambrano (Brazilian Neurosurgery)
Introduction The present study describes a case of an intracranial solitary fibrous tumor (iSFT) concurrent with meningioma in different anatomical regions.